Quality in laboratory medicine: an unfinished journey - Plebani, Mario (Journal of Laboratory and Precision Medicine; Vol 2 (August 2017): Journal of Laboratory and Precision Medicine, 2017)
Quality in medicine is an evolving concept, but currently the focus is on a patient-centered delivery of services and on the ultimate outcomes. In laboratory medicine, quality is moving from a simple focus on analytical quality toward global assessment of laboratory information, its real value in the clinical decision-making, so assuring valuable outcomes for patients and communities. The evidence collected in the last decades on the vulnerability of extra-analytical phases of the testing cycle requires developing and adopting quality indicators (QIs) covering the entire testing cycle, starting from the initial steps (test request, sample collection and transportation), to the analytical phase and, finally, to the correct interpretation and utilization of laboratory information (post-post-analytical phase), so finally improving diagnostic and therapeutic decisions.